C-reactive protein induced T cell activation is an indirect monocyte-dependent mechanism involving the CD80/CD28 pathway - Thomé, Julia; Limmer, Julia; Brose, Teresa Z.; Zeller, Johannes; Chevalier, Nina; Schäfer, Anna-Lena; Schneider, Laura; Lind, Maike; Christmann, Thierry; Dreck, Marie; Kreuzaler, Sheena; Braig, David; et al. (Frontiers in Immunology, 2025)
IntroductionT cells are major components of the immune system. Their activation requires interaction between the T cell receptor and co-stimulatory molecules, crucial during infection, inflammation, and allogeneic rejection. Monomeric CRP (mCRP) is a known modulator of inflammation and particularly the innate immune response, however its interaction with T cells as part of the adaptive immune response remains unclear.MethodsPeripheral blood mononuclear cells (PBMC) and T cells were isolated. Flow cytometric analysis was conducted to evaluate Fcγ receptor CD16 expression on T cells, the binding of CRP to T cells, and its impact on proliferation and apoptosis. T cell activation was assessed after 1, 2, 3, 5 and 7 days by assessing CD69 and CD25 expression, and under various conditions including coculture with monocytes and several inhibitory factors.ResultsT cells express CD16 that binds mCRP in a concentration-dependent manner, and particularly on activated T cells. While mCRP reduces apoptosis and accelerates proliferation in T cells, it does not independently activate them. However, activation of monocytes by mCRP leads to T cell activation, indicating a direct cell to cell interaction during CRP-induced activation. This effect could be alleviated by inhibition of the CD80/CD28 pathway.ConclusionCRP does not activate T Cells directly but via PI3-kinase-dependent activation of monocytes and subsequent CD80/CD28 cell to cell contact. The findings suggest the effects of CRP on T cells depend on their environment and the presence of other proinflammatory agents.